Studi Numerik Aliran Melintasi Empat Buah Silinder Sirkular Yang Tersusun In- Line Square Dengan Bodi Pengganggu - Yusup, Intan; Cut, Banta; Bahri Widodo, Syamsul (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
The development of circular cylinders in engineering has been widely utilized, including in pipeline construction, underwater networks, and tube heat exchangers. Previous studies have indicated the presence of drag forces, lift forces, vortex shedding, and vortex-induced vibrations (VIV) that occur when fluid flows past these cylindrical arrangements. Consequently, further research was conducted using numerical simulations aimed at reducing drag forces, lift forces, vortex shedding, and VIV in these circular cylinder configurations. In this study, four in-line square circular cylinders were arranged with a main cylinder diameter (D = 25 mm) and a disturbance body diameter (d = 4 mm), yielding a diameter ratio (d/D) of 0.16. The cylinder arrangement was placed in a narrow channel with a square cross-section measuring (H = 300 mm and L = 1500 mm), resulting in a blockage ratio of 25%, tested at a Reynolds number (Re) of 5.0 × 104 based on the cylinder diameter. Three disturbance bodies (DB) were positioned at angles θ = 0°, 120°, and 240° in front of two upstream cylinders with a gap distance (G/D) of 0.16 relative to the circular cylinder. This numerical simulation research was conducted using 2D UnsteadyRANS with Ansys Fluent 19.1 software, employing structured mesh and turbulence models k-ω-SST and K-Epsilon Standard. The results indicated that the distance between cylinders and the use of disturbance bodies significantly affect the drag coefficient experienced by the four in-line square circular cylinders. The addition of disturbance bodies surrounding the two upstream cylinders at angles of 0º, 120º, and 240º was highly effective in reducing the drag coefficient (CD) on the third cylinder (upper downstream) and the fourth cylinder (lower downstream).